MORPHOLOGY OF EXPERIMENTAL BREAST CANCER WITH METASTASIS TO THE LUNGS - Hasanov Komiljon Sunnatillaevich, (TADQIQOTLAR, 2025)
Abstract. Metastasis is the final stage of malignant progression; theoretically, a tumor of any size has metastatic potential. The biological nature of cancer and the characteristics of the host determine the possibility of further disease progression even after radical treatment. According to several authors, 12 to 30% of all lung and pleural tumors  are  metastatic.  This  review  focuses  on  the  comparative  morphology  of experimental breast cancer with lung metastasis.